Measuring the Impact of oil Revenues on Monetary Policy Tools in Iraq for the Period (2003-2023) - Kharief, Nacer; Alharbi, Mazin (Journal of Ecohumanism, 2024)
Monetary policy is the axis around which various economic policies revolve, despite their different intellectual approaches, due to its direct impact that overlaps with all economic aspects of society. Monetary policy gains its strength from controlling money, as the latter is the axis in employing specific resources to satisfy scarce needs, meaning that money is the essence of the economy, and other economic concepts are only reflections of it. Production is money that depends on the interaction of desire with ability, saving is money, investment is money, and even economic problems are money. Poverty is nothing but its scarcity, wealth is nothing but its abundance, and the absence of justice is nothing but its absence in distribution. However, this straight direction of monetary policy is exposed to many challenges that reflect a trend from a means of achieving economic prosperity to a tool for deepening economic backwardness, and the reflection of rentier behavior is one of them, and even the most important in particular. Therefore, to create a clear picture of the adverse impact of oil rents, we must stop at the station of rentier effects on quantitative tools, to know the level of influence or not, so that this standard model is the basic starting point for moving towards developing quantitative tools for monetary policy in the Iraqi economy after describing the levels of rentier reflection on the indirect tools of monetary policy in its two aspects, the general aggregate and the specialized detailed.